J.K. Lasser pro estate and business succession planning : a legal guide to wealth transfer - Fishkind, Russell J. (J.K. Lasser pro series., 2001)
Written by two attorneys who specialize in estate planning, this book clarifies all the issues involved in planning an estate and transferring wealth. It offers comprehensive estate planning guidelines, including creating a will, designating power of attorney, trusts, and life insurance, and includes up-to-date estate and inheritance tax information.